PENGARUH PENGGUNAAN ALAT PERAGA BILANGAN BERPANGKAT TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SDN 01 SEMANGET - Sukristin, Sukristin; Qomara, Dwi; Chintia, Helene; Yulita, Yulita (STKIP Melawi, 2024)
Abstract: The aim of the study was to determine the effect of the rank number teaching aids on the results of cognitive mathematics learning on the circumference and area of flat shapes for class IV B SDN 01 Semanget. Quantitative research method with a one group pretest-posttest design. The result showed that the average student learning outcomes increased by 82% after being given treatment. Wilcoxon test results with a = 0,025 obtained Zcount Ztable, namely -4,01 1,96. Because Zcount is in the areaof rejection of rejection of Ho, H1 is accepted, meaning that there is an effect of using rank number teaching aids on learning outcomes in mathematics. Based on from the analysis of the data it can be concluded that there is an effect of the use of graded teaching aids on theresult of learning mathematics in class IVSDN 01 Semanget.Keywords: Power Numbers Teaching Aids, Learning Outcomes, Mathematics.Abstrak: Tujuan penelitian untuk mengetahui pengaruh alat peraga bilangan berpangkat terhadap hasil belajar kognitif matematika materi keliling dan luas bangun datar kelas IV B SDN 01 Semanget. Metode penelitian kuantitatif dengan desain one group pretest-posttest design. Hasil penelitian menunjukkan Rata-rata hasil belajar siswa meningkat 82% setelah diberikan perlakuan. Hasil uji Wilcoxon dengan = 0,025 diperoleh Zhitung Ztabel, yaitu -4,01 1,96. Karena Zhitung berada di daerah penolakan Ho maka H1 diterima, artinya terdapat pengaruh penggunaan alat peraga bilangan berpangkat terhadap hasil belajar matematika. Berdasarkan analisis data dapat disimpulkan Terdapat Pengaruh Penggunaan Alat Peraga Bilangan Berpangkat Terhadap Hasil Belajar Matematika Kelas IV SDN 01 Semanget.Kata Kunci: Alat Peraga Bilangan Berpangkat, Hasil Belajar, Matematika.